2014
DOI: 10.1002/smll.201401262
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Perylene‐Based DNA Intercalator: Localization in Cell Nuclei and Inhibition of Cancer Cells and Tumors

Abstract: To date, perylene derivatives have not been explored as DNA intercalator to inhibit cancer cells by intercalating into the base pairs of DNA. Herein, a water-soluble perylene bisimide (PBDI) that efficiently intercalates into the base pairs of DNA is synthesized. Excitingly, PBDI is superior to the commercial DNA intercalator, amonafide, for specific nuclear accumulation and effective suppression of cancer cells and tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 63 publications
2
57
0
Order By: Relevance
“…Additionally, fluorescent multi‐cationic and amphiphilic PDI compounds have been used as gene‐delivery vectors and imaging reagents . Water‐soluble PDI and BPMI compounds have also been designed to study enzyme activity and DNA intercalation …”
Section: Methodsmentioning
confidence: 99%
“…Additionally, fluorescent multi‐cationic and amphiphilic PDI compounds have been used as gene‐delivery vectors and imaging reagents . Water‐soluble PDI and BPMI compounds have also been designed to study enzyme activity and DNA intercalation …”
Section: Methodsmentioning
confidence: 99%
“…Intercalating dyes find broad application in detection and quantification of nucleic acids, as well as therapeutics. For example, Xu et al synthesized a water-soluble PBDI and used it for nuclear intercalation and suppression of cancer cells and tumors (Xu et al 2014). Previously applied intercalating dyes have the disadvantage of high toxicity (e.g., EB).…”
Section: Intercalating Dyesmentioning
confidence: 98%
“…Non-covalently intercalating dyes represent a broad class of organic compounds (e.g., ethidium bromide (EB), perylene bisimide (PBDI), BODIPY, SYBR Green, and the recently introduced EvaGreen dyes), which change fluorescence properties upon intercalation into double-stranded nucleic acids (Xu et al 2014;Ikeda et al 2009;Brzezinska et al 2012;Zhao et al 2013;Morgan et al 1979;Ahn et al 1996;Miotke et al 2014). The main advantage of this class of dyes is their low cost and higher availability compared to other nucleoside-based sensors due to shorter synthetic route.…”
Section: Intercalating Dyesmentioning
confidence: 99%
“…Moreover, water soluble PDI molecules with biocompatibility and photostability have been successfully applied in the biological field [39]. Recently, PDI molecules were also attached to the DNA strand, at different locations [40,41,42,43,44]. Lewis and coworkers reported that PDI-linked bis(oligonucleotide) conjugates could form a hairpin dimer structure, driven by the hydrophobic interaction among PDI molecules [45].…”
Section: Small Molecules Modified Dnamentioning
confidence: 99%